Free vibration studies of box type laterite masonry structures - Unnikrishnan, Sujatha; Narasimhan, Mattur C.; Venkataramana, Katta (Journal of Structural Engineering, 2024)
Box-type laterite masonry structures are widely seen in south-west coastal areas of India. Not many studies are available in the literature on the dynamic response of such structures. Free vibration analysis of box-type laterite masonry structures has been attempted in this study, as a preliminary to a detailed dynamic analysis. Finite element analysis has been conducted to find the natural frequencies and corresponding mode shapes of box-type laterite masonry buildings. Results of detailed parametric studies conducted to find the effect of various parameters like modulus of elasticity of laterite masonry, provision of a lintel band or a roof slab, openings in long walls and aspect ratio on the natural frequencies and their mode shapes of box-type laterite masonry buildings are presented and discussed in this paper.